Cervical Spine Injuries with Acute Traumatic Spinal Cord Injury: Spinal Surgery Adverse Events and Their Association with Neurological and Functional Outcome. Issue 1 (1st January 2022) - Liebscher, Thomas; Ludwig, Johanna; Lübstorf, Tom; Kreutzträger, Martin; Auhuber, Thomas; Grittner, Ulrike; Schäfer, Benedikt; Wüstner, Grit; Ekkernkamp, Axel; Kopp, Marcel A.
Abstract : Supplemental Digital Content is available in the text This case-control study revealed associations of adverse events in spinal surgery with secondary complications, neurological recovery and dysphagia after traumatic injury to cervical spinal cord. In addition, length of stay and treatment costs were higher when spinal surgery adverse events occurred in patients with spinal fractures involving spinal cord injury. Abstract : Study Design: Monocenter case-control study. Objective: Effects of spinal surgical adverse events (SSAE) on clinical and functional outcome, length of stay, and treatment costs after traumatic cervical spinal cord injury (SCI). Summary of Background Data: Traumatic SCI is a challenge for primary care centers because of the emergency setting and complex injury patterns. SSAE rates of up to 15% are reported for spine fractures without SCI. Little is known about SSAE after traumatic SCI and their outcome relevance. Methods: Acute traumatic cervical SCI patients were enrolled from 2011 to 2017. Cases with and without SSAE were compared regarding neurological recovery, functional outcome, secondary complications, mortality, length of stay, and treatment costs. Adjusted logistic regression and generalized estimating equation models were calculated for the endpoints ASIA impairment scale (AIS)-conversion and dysphagia. All analyses were run in the total and in a propensity score matched sample. Results: At least one SSAE occurred in 37 of 165 patients (22.4%). Mechanical instability and insufficient spinal decompression were the most frequent SSAE with 13 (7.9%) or 11 (6.7%) cases, respectively. The regression models adjusted for demographic, injury, and surgery characteristics demonstrated a reduced probability for AIS-conversion related to SSAE (OR [95% CI] 0.14 [0.03–0.74]) and additionally to single-sided ventral or dorsal surgical approach (0.12 [0.02–0.69]) in the matched sample. Furthermore, SSAE were associated with higher risk for dysphagia in the matched (4.77 [1.31–17.38]) and the total sample (5.96 [2.07–17.18]). Primary care costs were higher in cases with SSAE (median (interquartile range) 97, 300 [78, 200–112, 300]) EUR compared with cases without SSAE (52, 300 [26, 700–91, 200]) EUR. Conclusion: SSAE are an important risk factor after acute traumatic cervical SCI with impact on neurological recovery, functional outcome, and healthcare costs. Reducing SSAE is a viable means to protect the limited intrinsic capacity for recovery from SCI. Level of Evidence: 4